Cultural heritage and nation branding – multi stakeholder perspectives from Portugal. Issue 5 (3rd September 2022) - Nobre, Helena; Sousa, Ana
ABSTRACT: This paper aims to explore how cultural heritage knowledge leverage country branding and contribute to developing a competitive identity. More specifically, we try to understand the role of visitor experiences and the community's engagement in this dynamic process. The study focused on Portugal's country brand and the Portuguese cultural heritage market. Based on the content analysis of the interview scripts of public decision-makers, museum/site managers, academics, and a tourism entrepreneur, the study offers exploratory findings regarding the roles performed by public entities and other institutions and the means used to attract visitors to heritage sites and encourage the engagement of the different 'actors' in cultural heritage experiences. Results indicate that cultural heritage represents a dimension of country identity and a driving factor of the tourism sector for Portugal.